Abyssal ascidians (Chordata, Tunicata) from the Weddell Sea, Antarctica, including a new Styela species and stomach content identifications - Maggioni, Tamara; Rimondino, Clara Mariana; Taverna, Anabela Jesús; Reyna, Paola Beatriz; Lagger, Cristian Fabian; Alurralde, Roque Gastón; Calcagno, Emilia; Tatian, Marcos (Zootaxa)
Deep-sea benthic communities from the Weddell Sea, Antarctica, were sampled in January–April 2005 in an area located between 61°S–70°S and 0°W–49°W. We found a total of eight ascidian species that belong to five different families, of which one corresponded to a new species. These were: Protoholozoa pedunculata Kott, 1969; Corynascidia suhmi Herdman, 1882; Styela andeepensis Maggioni & Tatián sp. nov.; Culeolus suhmi Herman, 1881; Culeolus anonymus Monniot F. & Monniot C., 1976; Culeolus likae Sanamyan K. & Sanamyan N., 2002; Oligotrema lyra (Monniot C. & Monniot F., 1973) and Asajirus indicus (Oka, 1913). We report: the extension of the known distribution ranges of P. pedunculata, Corynascidia suhmi, Culeolus suhmi, C. likae and A. indicus, being the first time they are collected from the Weddell Sea; and the shallowest record of C. likae. Six species were added to the list of ascidians of the Weddell Sea, being all deep-sea representatives. While the total number of ascidian species augmented from 43 to 49, the number of deep-sea representatives increased from 23 to 29. Our findings, thus, reinforce the need of performing more deep-sea prospections in the area. Las comunidades bentónicas de aguas profundas del Mar de Weddell, Antártida, fueron muestreadas entre enero y abril de 2005 en un área ubicada entre 61°S–70°S y 0°O–49°O. Encontramos un total de ocho especies de ascidias que pertenecen a cinco familias diferentes, de las cuales una corresponde a una nueva especie. Ellas fueron: Protoholozoa pedunculata Kott, 1969; Corynascidia suhmi Herdman, 1882; Styela andeepensis Maggioni & Tatián sp. nov.; Culeolus suhmi Herman, 1881; Culeolus anonymus Monniot F. & Monniot C., 1976; Culeolus likae Sanamyan K. & Sanamyan N., 2002; Oligotrema lyra (Monniot C. & Monniot F., 1973) y Asajirus indicus (Oka, 1913). Reportamos: la extensión de los rangos de distribución conocidos de P. pedunculata, Corynascidia suhmi, Culeolus suhmi, C. likae y A. indicus, siendo la primera vez que se ...